Acute mountain sickness (Medical Journal of Indonesia, 2001)
Acute mountain sickness, HAPE (high altitude pulmonary edema) and HACE (high altitude cerebral edema) are associated with acute exposure to altitudes greater than 8000 ft. Although usually self limiting, they can be life threatening. We are not yet clear abour the pathophysiological processes in acute mountain sickness. Descent to lower elevation is the definitive treatment for altitude illness. There is no unanimity of opinion regarding other modes of therapy. Treatment consists of bed rest, orygen inhalation and judicious use of morphine, diuretics, steroids and niftdipine as vasodilator therapy. (Med J Indones 2001; 10: 115-20) Keywords: Acute mountain sickness, high altitude pulmonary edema, high altitude cerebral edema